OPEN ETSAB. Experimenting from altered teaching. - López-Bravo, Celia (RU Books, 2018)
What happened at the School of Architecture of Barcelona during the second semester of the academic year 2012-2013 had its origin in a grassroots movement that produced, among other proposed projects, a type of teaching methodology which is still evolving. It is worth using a few lines to place in a context the moment at which this process took place. During the previous year, 2012, there had been several meetings in which students and teachers had joined in protest seeking to guarantee the quality of the public university. Among the main reasons for the protest were the meagerness of the teachers’ salaries (Ibáñez, 2012), the rise in registration fees and the tense situation created by the implementation of the Bolonia Process (Badia, 2013). That was how the ETSAB enlluita was born (ETSAB enlluita, 2013a).
Aporta autorización de la editorial.
Keywords: Arquitectura - Estudio y enseñanza superior; Investigación activa en educación; Alteración; Protesta; Innovación docente; Métodos docentes alternativos